Observing Family: A Technique to Teach Organizational Behavior Practically During Pandemic - Adhikari, Pralhad (International Research Journal of MMC, 2022)
Organizational Behaviour truly depends on the family legacy and the environment provided. This study aims to explore the connection of the students’ organizational behavior during the pandemeic. A qualitative research was conducted using exploratory design. The archival and diary method of data collection was implied. The secondary data of assignments submitted by the students of BHM from a college in Kathmandu were used. The students submitted their diaries after observing their families for two weeks and recording the observed activities once every two days. The data were analyzed using a content analysis approach. The students presented interesting examples for various OB concepts like perception, attitude, motivation, satisfaction, conflict, and change. The study justifies that the students in family can better foster their organizational behavior than the learning of the theoretical content at college.